A Premature Infant With Neonatal Actinomyces odontolyticus Sepsis. (2nd November 2020) - Rueda, Maria S; Hefter, Yosefa; Stone, Brian; Hahn, Andrea; Jantausch, Barbara
Abstract: We describe the presentation, diagnosis and management of a premature newborn with Actinomyces odontolyticus bacteremia; this is the first case report of neonatal sepsis secondary to this bacteria. Maternal dental infection was the likely source of the pathogen. The outcome was favorable, with good response to antimicrobial therapy with ampicillin/amoxicillin.